Mapping the social space of transnational migrants on the basis of their (supra)national belongings: the case of French citizens in Berlin. Issue 2 (3rd March 2016) - Duchêne-Lacroix, Cédric; Koukoutsaki-Monnier, Angeliki
Abstract : In traditional migration theory, social self-identification is usually linked with the process and quality of integration and with the nationality of the countries of 'origin' and of residence. But in the context of a supranational integrated area like the European Union, the self-identification of European people living (also) abroad in another European country can be more complicated. What sorts of identity combinations do they produce in this situation? Could we interpret their choice in the light of their social, economic, cultural capitals and (multi)local integration? Based on an empirical analysis of French citizens in Berlin this article confirms that identity self-combining – not just the identity elements – and the position of the ego in the social space are related. The meaning of the same identity category depends on the respondent's profiles.